2014
DOI: 10.1038/srep05436
|View full text |Cite
|
Sign up to set email alerts
|

Assortative mating between two sympatric closely-related specialists: inferred from molecular phylogenetic analysis and behavioral data

Abstract: Host plant shifting of phytophagous insects can lead to the formation of host associated differentiation and ultimately speciation. In some cases, host plant specificity alone acts as a nearly complete pre-mating isolating barrier among insect populations. We here test whether effective pre-mating isolation and host-independent behavioral isolation have evolved under the condition of extreme host specilization using two sympatric flea beetles with incomplete post-mating isolation under laboratory conditions. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…female vs male choice) give different I PSI values and similar variation has been reported in previous studies233739. This is consistent with the hypothesis that the degree of reproductive isolation varies under different mating systems, and therefore, experimental designs3745.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…female vs male choice) give different I PSI values and similar variation has been reported in previous studies233739. This is consistent with the hypothesis that the degree of reproductive isolation varies under different mating systems, and therefore, experimental designs3745.…”
Section: Discussionsupporting
confidence: 90%
“…The mating patterns and degree of sexual isolation between the W and R populations in different choice tests were estimated by the pair total index (PTI) and joint isolation index (I PSI )3739. The PTI estimates whether the mating pattern of each pairing is different from random mating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ohshima ; Xue et al. ), providing a mechanistic explanation of how host shifts may promote speciation. Understanding the role of host plant shifts in generating diversity is thus a current focus in the study of herbivorous insect diversification (Marvaldi et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a classical study by Farrell (1998) showed that herbivorous insects using angiosperms as hosts are more species rich than those using gymnosperms among the Phytophaga beetles, suggesting that the diversity of angiosperms has facilitated speciation by host shift in the beetles that feed on them. Studies of host races in herbivorous insects showed that specialization to a novel host plant sometimes results in reproductive isolation between insects using different hosts (Feder et al 1988;Groman and Pellmyr 2000;Hawthorne and Via 2001;Nosil et al 2002;Thomas et al 2003;Malausa et al 2005;Ohshima 2012;Xue et al 2014), providing a mechanistic explanation of how host shifts may promote speciation. Understanding the role of host plant shifts in generating diversity is thus a current focus in the study of herbivorous insect diversification (Marvaldi et al 2002;Stireman et al 2005;Wheat et al 2007;Winkler et al 2009;Fordyce 2010;Funk 2010;Matsubayashi et al 2010;Nyman 2010;Soria-Carrasco et al 2014).…”
Section: Introductionmentioning
confidence: 99%